2017
DOI: 10.1111/jch.12986
|View full text |Cite
|
Sign up to set email alerts
|

Low dose‐eplerenone treatment decreases aortic stiffness in patients with resistant hypertension

Abstract: Vascular damage is aggravated in animal models of hypertension with mineralocorticoid (MR) excess and in hypertensive patients with primary hyperaldosteronism. MR antagonism has shown to provide effective blood pressure (BP)‐control in patients with treatment resistant hypertension (TRH), but the concurrent effects on the vasculature have not been examined. In a randomized, double‐blinded, placebo‐controlled parallel‐group study, 51 patients with TRH received either eplerenone 50 mg or placebo for 6 months tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
(63 reference statements)
0
8
1
Order By: Relevance
“…It is likely that change in SBP with eplerenone treatment contributes to the decrease in PWV. There is a discrepancy between the effect of miner-alocorticoid receptor antagonists on arterial stiffness in patients with IHA and the results of our study and that previous study [33]. Some possible reasons for the discrepancy are postulated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is likely that change in SBP with eplerenone treatment contributes to the decrease in PWV. There is a discrepancy between the effect of miner-alocorticoid receptor antagonists on arterial stiffness in patients with IHA and the results of our study and that previous study [33]. Some possible reasons for the discrepancy are postulated.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, medical treatment with spironolactone did not improve PWV in patients with primary aldosteronism, including IHA and an unknown subtype of primary aldosteronism. Kalizki et al [33] reported that treatment with eplerenone decreased PWV in patients with resistant hypertension. However, the effect of eplerenone on arterial stiffness in patients with IHA is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, besides lowering BP, aldosterone antagonist has documented pleiotropic effects including improving endothelial function, anti-inflammation and antifibrosis. [ 21 23 ] Therefore, one may anticipate that spironolactone treatment would be better than HCTZ for arterial stiffness improvement and BP control. Results from the present study support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of cPWV under treatment, as documented at follow-up in a small subset of PA patients in our study, may be a hint on the effect of aldosterone excess on vascular aging via arterial stiffening. Although it is of note that the reduction of cPWV and albuminuria have also been reported in patients with (essential) hypertension on MRA treatment, which should promote a more liberal use of MRA in patients with arterial hypertension [32,33].…”
Section: Patient Characteristicsmentioning
confidence: 95%